New Remedies from Natural Products in Brain Stroke - Pandey, Haushila Prasad; Mishra, Vaibhav; Akanksha, Dr. (Journal of Universal College of Medical Sciences, 2018)
Acute ischemic stroke is the third leading cause of death and the most frequent cause of permanent disability. Despite advances in the understanding of the pathophysiology of cerebral ischemia, therapeutic options remain limited. Only recombinant tissue-plasminogen activator (rt-PA) for thrombolysis is currently approved for use in the treatment of stroke. However, its use is limited by its short therapeutic window (three hours), complications derived essentially from the risk of haemorrhage, and the potential damage from reperfusion/ischemic injury. Two important pathophysiological mechanisms involved during ischemic stroke are oxidative stress and inflammation3. On the basis of pre existing literatures, brain tissue is not well equipped with antioxidant defenses. So for a future candidate drug that may able to cure the stroke it must have anti oxidant and anti inflammatory properties. This review will discuss the molecular and biochemical aspects of oxidative stress and inflammation in ischemic stroke that targets neuro-inflammation through natural products.Journal of Universal College of Medical Sciences (2016) Vol.04 No.02 Issue 14, page: 35-39